A Novel 7-Days Prolonged Dietary Deprivation Regimen Improves ALT and UA After 3–6 Months Refeeding, Indicating Therapeutic Potential - Wang, Xiaoxue; Li, Zhihui; Zhao, Yancong; Yu, Yaying; Xue, Yanyan; Niu, Chenguang; Wei, Qiannan; Zhao, Zhijun; Cai, Shangyuan; Xu, Hongxia; Zhang, Chenlu; Zhang, Chenggang; et al. (Frontiers in Nutrition, 2020)
Objectives: The aim of this study was to evaluate a novel prebiotic, Flexible Abrosia (FA), assisted total fasting regimen for more than 7 days’ continual dietary deprivation (7D-CDD). Our analysis included basic physical examinations, bioelectrical impedance analysis, clinical lab and ELISA analysis in normal volunteers. Methods: Seven healthy subjects with normal bodyweight participated in 7D-CDD under the assistant of specially designed probiotic. Individuals were assigned to take FA (113.4KJ/10g) at each mealtime to avoid possible injuries from intestinal flora and smooth the hunger sensation. During 7D-CDD, the subjects were advised to avoid any food intake, especially carbohydrates, except plenty of water supply. The examination samples were collected at before CDD as self-control, fasting 7thD and after 7~14D refeeding. Three subjects were also tested after 6M’s refeeding. Results: The FA-CDD regimen significantly released suffering of starvation with tolerable hungry sensation during the treatment. With the addition of daily mineral electrolytes, the subjects not only passed through the entire 7D-CDD regimen but also succeed in 12~13D total fasting in 2 subjects. Except significant reduction in blood glucose, insulin and high-density lipoprotein level during fasting, the blood concentrations of uric acid (UA), alanine aminotransferase (ALT), and creatine kinase (CK) were also increased. However, after more than 2 months’ refeeding, the disease markers such as ALT, GOT and CK either remained stable or slightly downregulated comparing with their initial 0D control level. Conclusion: Our experiment has supplied the first beneficial evidence that, with the assistant of nutritional flora daily supply of less than 100Kcal total calorie, human subjects were tolerable in hunger sensation. We have found that, although during 7D-CDD induced increases in UA, CK and transferases, refeeding led the markers either downregulated or unchanged. This phenomenon was further confirmed in longer term (6M) recovery. Our results failed to support the hypothesis that fasting induced liver damage since ALT, GOT and CK remained low after longer-term refeeding. Our finding indicated that the 7D-CDD regimen might to be practical, and it might be valuable to design larger clinical trials of fasting study in health improvement strategy targeting in metabolic disorders.